Pengaruh Indikator Pertumbuhan Ekonomi terhadap Kualitas Lingkungan Hidup Provinsi di Pulau Sumatera - Rahma Nurhamidah; Endan Suwandana (Publikasi Penelitian Terapan dan Kebijakan, 2023)
The environmental quality of Sumatra Island, which is the second pillar of the Indonesian economy, is threatened to deteriorate. The uncertain development of environmental quality and the potential for economic activities that threaten environmental sustainability make the environmental quality of provinces on the Sumatra require more attention. This study aims to analyze the effect of economic growth indicators on environmental quality in 10 provinces on the Sumatra islands. This study uses panel regression analysis data method. The unit of analysis in this study was ten provinces on the island of Sumatra in 2015-2020. The analytical method used in this study is descriptive analysis with quadrant analysis techniques and inferential analysis through panel data regression. Research findings using quadrant analysis show that two of the ten provinces are classified as advanced or superior in income, investment, and environmental quality. Regression analysis using the fixed effect model (FEM) shows that increasing economic growth can reduce the environment that indicated by the negative and significant effect of indicators economic growth GRDP and PMTB, on environmental quality. It was Concluded that efforts are needed to tighten environmental protection regulations, strengthen investment policies and laws, and socialize relevant stakeholders about environmental care to avoid environmental damage and environmental degradation.